2019
DOI: 10.5194/tc-13-1089-2019
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of ice-wedge degradation in polygonal tundra under different hydrological conditions

Abstract: Ice-wedge polygons are common features of lowland tundra in the continuous permafrost zone and prone to rapid degradation through melting of ground ice. There are many interrelated processes involved in ice-wedge thermokarst and it is a major challenge to quantify their influence on the stability of the permafrost underlying the landscape. In this study we used a numerical modelling approach to investigate the degradation of ice wedges with a focus on the influence of hydrological conditions. Our study area wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
167
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(192 citation statements)
references
References 49 publications
8
167
0
Order By: Relevance
“…In this study, we modify CG3 to improve the water balance and evapotranspiration scheme as described below. The version of CG3 used in Nitzbon et al () includes the same modifications.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we modify CG3 to improve the water balance and evapotranspiration scheme as described below. The version of CG3 used in Nitzbon et al () includes the same modifications.…”
Section: Methodsmentioning
confidence: 99%
“…From the former, a detailed conceptual model has been developed in which thermokarst may follow any of several trajectories, which vary according to how severely an ice wedge melts before it is stabilized by organic matter accumulation or trough drainage. Inspired by this conceptual model, several investigations in the past several years have begun exploring process‐rich, physically based computer simulations as a means of capturing ice wedge dynamics at large spatial and temporal scales (Aas et al, ; Jan et al, ; Nitzbon et al, ). To date, these simulations have captured some essential components of thermokarst—such as an initial acceleration of melting as thermokarst pools develop, followed by a gradual deceleration—but in each case, the models have employed a highly simplified representation of polygonal microtopography.…”
Section: Introductionmentioning
confidence: 99%
“…1b;Boike et al, 2013Boike et al, , 2018). All degradation stages described by Liljedahl et al (2016) can be found here, from non-degraded low-centered polygons to high-centered polygons with connected troughs (see Nitzbon et al, 2018). Between 1997 and 2017 the mean annual air temperature at the island was approximately -12.3 °C, with an annual liquid precipitation of 169 mm and mean end-of-winter snow depth of 0.3 m (Boike et al, 2018).…”
Section: Samoylov Island Northern Siberiamentioning
confidence: 81%
“…These are in reality of different sizes and shapes ( Fig. 1), but can to a first approximation be considered a selfrepeating pattern, as also described by Nitzbon et al (2018). Due to symmetry, a larger region can then be represented as a single feature with a representative geometry, where the interaction between the different polygons can be ignored.…”
Section: Polygonal Tundra On Samoylov Island Northern Siberiamentioning
confidence: 99%
See 1 more Smart Citation